OPTIMASI PERTUMBUHAN MIKROALGA CHLORELLA VULGARIS YANG BERPOTENSI SEBAGAI AGEN UPGRADING BIOGAS MENJADI BIOMETANA - Alfa Arina, Linea
Palm oil industries in Indonesia produce abundant waste known as Palm Oil Mill Effluent (POME), reaching 50-60% from total palm oil production. Recently, POME has been converted into biogas due to it’s rich organic compounds. Biogas from POME faces some production challenges, such as low energy density compared to natural gas and still contains some impurity such as CO2, H2S, volatile fatty acids, and water vapor, thus hindering direct use as a fuel. Therefore, it is needed to employ process to increase the heating value of biogas. Biogas upgrading technology from POME using biological agents such as microalgae has been established due it’s energy saving and environmentally friendly. Utilizing the abilities of microalgae on photosynthesis and carbon capture storage, CO2 in biogas can be removed and it can be used as a carbon source for biomass production. One of the microalgae that has the potential to be used in this case is Chlorella vulgaris. It can grow in biogas organic matters with high productivity. Moreover, Chlorella vulgaris is CO2 tolerant. Therefore, this research was conducted to optimize the growth of Chlorella vulgaris as a potential agent to upgrade biogas into biomethane. In this research, the growth of Chlorella vulgaris was optimized based on two main growth factors, i.e several light wavelengths (visualized by red, blue, and white light) and the carbon source, using an inorganic CO2 source, NaHCO3 in different concentration (0;1;2; 3 g/l) to observe the ability of Chlorella vulgaris in CO2 biofixation. 10% (v/v) inoculum of Chlorella vulgaris was grown in Bold’s Basal Medium for 18 days, at temperature room (25±0,6oC), with initial pH 6,6, used photoperiods 16:8, and placed on 150 rpm rotary shaker. Chlorella vulgaris biomass, pH changes and chlorophyll a and b pigments are determined. Biomass production was analyzed using spectrophotometric method at ?=680 nm. Chlorophyll a and b pigments were also analyzed by spectrophotometric method using ?=630 nm, ?=645 nm, and ?=665 nm based on Parson&Strickland method. Results showed the best inoculum was reached on the 8,5th day of culture. The highest growth rate and biomass was obtained using light wavelengths at range 450-495 nm (visualized by blue light) with the added of 2 g/l NaHCO3. These combinations also resulted the highest number of Chlorophyll a and b, 4.24 mg/l and 3.08 mg/l, respectively. Therefore, it can be concluded that the light wavelength had significant effect on Chlorella vulgaris production, especially for the blue-light treated, reaching growth rate was 0,195 day-1. Adding different concentration of NaHCO3 resulted no significant effect on biomass production.